Konvekcii kak osnova ispolneniâ socialʹnyh i kommunikativnyh rolej v delovom dialogičeskom obŝenii - Koltunova, Mariâ V. (Stylistyka, 2021)
Conventional behavior in business communication characterizes complex obligatory control speech norms, pragmatic restrictions and prohibitions, complicated and strengthened by social behavior rules and norms. Regulation information density and portioning information, cognitive process control, on the one side, and coordination mode of attitudes and emotions coordination, on the second, organize the interaction processes in business dialogs. They structured and organized communication according the purposes of participants. Official interaction zone claim more strong control to observe conventional rules and norms then nonofficial and half-officia! ones. They structured and organized communication and uses as a basis of producing communicative and social roles in business communication. It does realize by illocutionary stereotype schemes of genre situational script.